Space and Unemployment: The Labor‐Market Effects of Spatial Mismatch - Brueckner, Jan K.; Zenou, Yves (Journal of Labor Economics, 2003)
The aim of this article is to analyze the effects of housing discrimination on the wages and unemployment rates of black workers. The unemployment effect is first analyzed using a simple minimum‐wage model. An efficiency‐wage model is then adopted in order to endogenize both unemployment and wages. Under both models, suburban housing discrimination leads to a higher unemployment rate for blacks in the central city than in the suburbs. Under the efficiency‐wage model, black wages are also lower in the center. The analysis thus generates a link between unemployment and a seemingly unrelated phenomenon: racial discrimination in the housing market.